Urgensi Leadership Dan Manajerialship Kepala Sekolah dalam Meningkatkan Kinerja Sekolah - Kustiono Kastaji; Achmad Patoni; Binti Maunah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of writing this work is to describe the Urgency of Leadership and Managerialship of School Principals in Improving School Performance. This research uses a literature review method to analyze the urgency of school principal leadership and managerial leadership in improving school performance. This method collects and analyzes information from various relevant sources to gain an in-depth understanding of the topic being discussed. Through this approach, researchers can identify patterns, themes, and gaps in the literature to formulate practical recommendations for school principals in increasing student motivation, reducing school dropout rates, and increasing participation in extracurricular activities. The results of this work are that effective leadership and management are very important to improve school performance through reward systems, mentorship programs, and collaboration with parents. Education about the dangers of online game addiction and providing interesting extracurricular activities can help students stay focused on academics. Financial assistance, teacher training, and partnerships with local communities are also needed to overcome barriers and improve the quality of education. Improved infrastructure and integration of technology in learning supports a conducive learning environment, while ongoing monitoring and evaluation ensures the effectiveness of school programs.